SIGHT-GLASS DEGRADATION IN UREA CARBAMATE SOLUTION - Dikdik Yuliana; Hengki Irawan (Indonesian Journal of Engineering and Science (IJES), 2022)
In the industrial environment, a sight glass acts as a gauge for the fluid level in a pressure vessel. Sight glass must have the following physical properties: clarity (clear enough to view the fluid in the vessel), hardness (not easily broken), thermal shock resistance, and corrosion resistance. A historical investigation of the equipment placed in the High-Pressure Decomposer (HPD) unit of the Urea Plant-X and Plant-Y has a pressure of 17 Bar and a temperature of 124-155oC, yielded an analysis of sight glass degradation in carbamate solution. The sight glass that was installed is soda-lime fused glass. The average is based on the equipment's history.